2021
DOI: 10.3389/fevo.2021.641740
|View full text |Cite
|
Sign up to set email alerts
|

Survival Sounds in Insects: Diversity, Function, and Evolution

Abstract: Insect defense sounds have been reported for centuries. Yet, aside from the well-studied anti-bat sounds of tiger moths, little is understood about the occurrence, function, and evolution of these sounds. We define a defense sound as an acoustic signal (air- or solid-borne vibration) produced in response to attack or threat of attack by a predator or parasitoid and that promotes survival. Defense sounds have been described in 12 insect orders, across different developmental stages, and between sexes. The mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 178 publications
(173 reference statements)
0
28
0
Order By: Relevance
“…Thus, the net individual benefit-cost ratio of signaling is considered to be larger in males, and the evolution of signaling will be easier in males. A recent literature survey on the defensive sounds in insects by Low, Naranjo, and Yack (2021) suggested that the sex that use antipredator signals is usually males when only one sex in a species signals. A part of our finding is consistent with those in previous studies on sexual dimorphism demonstrating that the intrinsic differences between sexes brings dimorphic niches of traits, leading to the evolution of sexual dimorphism (Rice 1984;Lande 1980;Slatkin 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the net individual benefit-cost ratio of signaling is considered to be larger in males, and the evolution of signaling will be easier in males. A recent literature survey on the defensive sounds in insects by Low, Naranjo, and Yack (2021) suggested that the sex that use antipredator signals is usually males when only one sex in a species signals. A part of our finding is consistent with those in previous studies on sexual dimorphism demonstrating that the intrinsic differences between sexes brings dimorphic niches of traits, leading to the evolution of sexual dimorphism (Rice 1984;Lande 1980;Slatkin 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The function of crepitation in most species of Acrididae has not been revealed yet. One hypothesis is that crepitation is an antipredator signal (Edmunds 1974;Low et al 2021). Another hypothesis is that crepitation is a signal to conspecifics for reproduction (Otte 1970;Elsner & Wasser 1995;Niedzlek-Feaver 1995;Berger 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Sound is produced by many insects as a defense against predators (Low et al 2021). The sound produced by many species of grasshoppers when they escape by flying (Willey & Willey 1969;Otte 1970) is also considered to be an antipredator defense.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once a predator has been detected, orthopterans may react defensively to try and avoid being captured, such as switching to low-intensity song so only a nearby mate can hear, stopping singing completely for a time (e.g. ter Hofstede et al, 2010), and/or producing a defensive sound (a noise directed at a predator that improves the chances of survival; for a review of defensive sounds see Low et al, 2021). Haglids in the genus Cyphoderris have an unusual stridulatory method of producing a defensive sound, probably directed at ground predators, using Ander's organ (Woodrow et al, 2021).…”
Section: Natural Enemies: Risks and Defencesmentioning
confidence: 99%